Perencanaan Rute dan Kecepatan AGV pada Sistem Pergudangan Menggunakan Algoritma Ant Colony Optimization - Pamosoaji (Universitas Katolik Musi Charitas, 2019)
This paper discusses a modifiedalgorithm of route planning and speed of a group of Automated Guided Vehicle (AGV) in a warehousing system. Given an AGV group that carries material out of the warehouse. This algorithm has to decide which routes and speed are applied so that all AGVs can reach the target point without any collision to each other. In addition, the slowest travelling time from AGV must be minimized. Each AGV has a maximum speed limit. The warehouse used as a case study is a simple warehouse that is modeled as a 15-point matrix. The method applied is a modified Ant Colony Optimization (ACO) algorithm. In the ACO algorithm, two solutions can be combined: route determination from point to point and speed that must be applied by the AGV on the route between any two points. The ACO algorithm is used to determine the speed of point-to-point travel. By this method, collision among vehicles can be avoided. The simulation results revealthe performance of the proposed algorithm for a simple warehouse is quite satisfying. This conclusion is indicated by the convergence of the minimum travel time generated from faster vehicles and the routes resulting from collision-free requirements.